Immersive pedagogy in History: Cognitive scaffolding and affective growth - Nurul Asyikin Hassan; Mohd Nazir Md. Zabit; Septian Aji Permana; Siti Zahrah Mahfood; Dg. Junaidah Awang Jambol (LPMPP Universitas Negeri Yogyakarta, 2026)
This research investigates the integration of VR-Mnemonics as a targeted pedagogical innovation for History instruction within the Malaysian secondary education context. Utilizing a single-site qualitative case study design, the study focused on three (N=3) Form 5 students at a residential school in Sabah. Informants were purposively selected based on a profile of persistent academic underperformance and failure in national-level History assessments. Data were derived from multiple sources, including document analysis of learning artifacts and student reflective notes. Applying a reflexive thematic analysis, the study identified that the intervention effectively addressed the limitations of conventional instruction by improving both factual retention and cognitive interest. Core findings indicate a remarkable qualitative improvement in the students' academic trajectory, particularly in mastering complex historical chronologies and demonstrating advanced historical reasoning. Emerging themes highlighted the tool’s capacity for immersive cognitive scaffolding and its role in transforming student attitudes toward a traditionally